Factors Affecting Success of ERP (Enterprise Resource Planning) System Implementation - Erwanto, Elyus Dwi; Zusi, Hasmand (Universitas Mercu Buana, 2020)
This study aimed to determine the factors that influence the successful (critical successfactors) of ERP implementation in the company's client PT. Artsys Integrasi Solusindo. The data used are primary data using questionnaires from respondents. This research was conducted on 13Â companies that have implemented ERP, with 80 respondents being used as samples. The sampling method in this study uses non-probability sampling with a quota sampling technique based on criteria. The analytical tool used in this study is regression analysis. The research hypothesis testing was completed using t-test, F-test and descriptive analysis. The results of this study indicate that Change Management, Project Management, Top Management Sponsorship, Realistic Scope Setting, and Adequate Budget are factors that influence the success of ERP implementation. While the factor of Education in an ERP project does not have a significant effect. But simultaneously, the six factors can explain the relation to the success of ERP implementation with the R-square value of 67.6%. With this research, it is expected that ERP consultants and implementers and the companies that are currently and will implement ERP to pay attention and prepare well the factors that determine the success of ERP implementation.